2009
DOI: 10.1002/smll.200900135
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Magnetic Colloids: A Strategy to Form Complex Structures Using Nonspherical Building Blocks

Abstract: Microscopic magnetic particles dispersed in a solvent-or dipolar colloidal fluids-commonly assemble into chains due to a directional attractive interparticle potential. These chained structures can impart optical anisotropy (i.e., birefringence) to dipolar fluids, [1] and have been demonstrated as effective matrix materials in the rapid separation of DNA using microfluidic electrophoresis. [2] In the special case of magnetorheological (MR) systems, which require external fields to induce dipoles in polarizable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 32 publications
4
78
0
Order By: Relevance
“…(d) Twisted columns of stacked peanut-shaped particles. Reproduced with permission, [ 223 ] copyright 2009 Wiley. (e) Lock and key assembly of polymer particles.…”
Section: Fabrication and Assembly Of Anisotropic Particlesmentioning
confidence: 98%
“…(d) Twisted columns of stacked peanut-shaped particles. Reproduced with permission, [ 223 ] copyright 2009 Wiley. (e) Lock and key assembly of polymer particles.…”
Section: Fabrication and Assembly Of Anisotropic Particlesmentioning
confidence: 98%
“…Hematite also possesses a magnetic moment (due to canted antiferromagnetism [21][22][23][24] ) that induces dipole-dipole attractions. To obtain a stable self-assembling system of hematite cubes a balance between the van der Waals and magnetic attraction and the double layer repulsion has to be found.…”
Section: Cube Propertiesmentioning
confidence: 99%
“…Here, we investigate the organization of micron-sized cubelike hematite (a-Fe 2 O 3 ) colloids with a permanent magnetic dipole [21][22][23][24] into three dimensional (3D) structures as a function of inter-cube interactions and external elds. The effect of particle shape, surface charge and alignment in a magnetic eld on the resulting self-assembled structures is investigated.…”
mentioning
confidence: 99%
“…This opens perspectives for magnetic nanofluids with specific rheological properties and as complex building units for the next level in hierarchy of material design. Promising studies in this direction were already reported based on micron-sized particles with complex shapes [56][57][58].…”
Section: Hybrids With Complex Shapesmentioning
confidence: 97%